Alkoxycarbonylation of olefins with carbon dioxide by a reusable heterobimetallic ruthenium–cobalt catalytic system. Issue 24 (23rd November 2018) - Zhang, Xuehua; Shen, Chaoren; Xia, Chungu; Tian, Xinxin; He, Lin
Abstract : The heterobimetallic ruthenium–cobalt catalytic system exhibited good catalytic performance and reusability in the reductive alkoxycarbonylation of olefins with CO2 . Abstract : The heterobimetallic ruthenium–cobalt catalytic system exhibited good catalytic performance and reusability in the reductive alkoxycarbonylation of olefins with carbon dioxide. Compared to the previous system only consisting of ruthenium catalyst, the binary catalyst system effectively reduced the usage of noble metal and ionic liquid additives. The respective contribution of ruthenium and cobalt catalysts in this multiple-step catalytic process was investigated by a series of condition-controlled experiments. The evolution of the ruthenium catalyst and the occurrence of alkene hydrogenation during the reaction was explained by theortical calculations.